If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5.6 + 12.2 = 5h Combine like terms: -5.6 + 12.2 = 6.6 6.6 = 5h Solving 6.6 = 5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-5h' to each side of the equation. 6.6 + -5h = 5h + -5h Combine like terms: 5h + -5h = 0 6.6 + -5h = 0 Add '-6.6' to each side of the equation. 6.6 + -6.6 + -5h = 0 + -6.6 Combine like terms: 6.6 + -6.6 = 0.0 0.0 + -5h = 0 + -6.6 -5h = 0 + -6.6 Combine like terms: 0 + -6.6 = -6.6 -5h = -6.6 Divide each side by '-5'. h = 1.32 Simplifying h = 1.32
| 4(m-3)=-32 | | 4x+6x+1=0 | | x^2-5=sqrt(3*x) | | -23-2p=19-p | | 12x^2+35x-3=0 | | 7=9(2f+5) | | 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 | | 18=a(a-7) | | 4x=14x-30 | | 6b+15=4b+19 | | -84=-7(x+5) | | (6x+2)+20=360 | | 20+.5= | | bing=-2 | | -20=-4x+-6x | | -5.6+12.2=5 | | 2x+3(2x-9)=(4x+3) | | (6x+2)+20=180 | | 5a+6=-8 | | 8x-2x+66=8x+26 | | 2y-4=-10x | | 5y-60332=600y+422 | | -7+2h=-15 | | 2(4b-6)+6(-3-2b)=6-4b+4-5b | | 3x+9=-6x+16 | | 4x+6=y-3 |